Wahbah Zuhaili’s and Sayyid Sabiq’s Perspective on The Principles of Marriage Contract in Indonesia - Hafidzi, Anwar; Mohd. Hani, Mohd Hatta (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study discusses pronunciations used in marriage contracts in Indonesia with various types of pronunciation. The jurisprudence experts agree to use the words